Os impactos da vida acadêmica na religiosidade dos universitários da UNIMONTES nas áreas do conhecimento: Humanas, Exatas, Tecnológicas, Biológicas e da Saúde - Quadros, Cláudia Simone Pereira Sarmento (2016)
To analyze the impacts of academic life in the religiosity of college students at the State University of Montes Claros Unimontes, in the areas of Exacts, Technology, Humanities, Biology and Health. Rationale: The State University of Montes Claros − Unimontes − is a major catalyst focus of montesclarense education and culture and does not have any indicator on the impact of the university in the students religiosity. Hypotheses: it was meaningful to question the impacts caused by the students admission at the university from the perspective of the following hypotheses: the impacts experienced by students as a result of a secularized academic life interfere with their religiosity; the students religiosity nowadays, at the university locus, seems individual and subjective, no longer tied to the principles of religious and family institutions; the impacts of college life in the students religiosity, by field of knowledge, take place in different ways and intensities, considering the three academic fields. Theoretical and methodological aspects: Given the characteristics of the original idea, the option was to perform a qualitative and quantitative research on a descriptive and exploratory approach with the help of library and field research. With regards to the written sources, we have chosen especially: Taylor (2010), Berger (1985; 2001), Hervieu-Léger (2005), Martelli (2002), Ribeiro (2009) and Pierucci (2000). For the field research we have made use of a questionnaire and a group interview with the technique of focal group. The place within the study was the Unimontes. The study has included 430 registered and frequent students at the courses of the fields of Exact and Technologic Sciences, Humanities, and Biological Sciences and Health. Results: statistically, the data has revealed that the admission at the university had not changed the religious affiliation but had changed the frequency at the church because of the demands of college life. There has been noticed the relativity of religious affiliation, brought about by the possibility of free choice as well as by the influences exerted by the academic environment which is characterized by the development of science and a critical and skeptical spirit